Key Considerations for Frail Patients Undergoing Hip Fracture Surgery - Ana-Maria Dumitriu; Rǎzvan Ene; Liliana Mirea (Clinics and Practice)
Improving preoperative care for elderly patients with hip fractures is crucial for achieving the best outcomes. A multidisciplinary team that can improve overall care quality by addressing patient’s medical conditions, analgesia, timely surgery, and early postoperative mobilization is required. This narrative review provides insights regarding the extent of preoperative optimization needed for hip fracture surgery.